Arduino Uno-Based Vibration Monitoring System Design Using The Sensor Mpu5060 - Alwin Juhendra; Razali (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
The development of manufacturing technology demands a machining process that produces high-quality and precise products. In the turning process, machine vibration is one of the factors that affect the quality of machining results, component life, and process stability. Excessive vibration can lead to a decrease in the surface quality of the workpiece as well as accelerate the wear of machine components. Therefore, a monitoring system is needed to effectively monitor the condition of engine vibration. This research aims to design and build an Arduino Uno-based lathe vibration monitoring system using MPU6050 sensors. The sensor is used to detect vibrations, while the Arduino Uno functions to process the measurement data. Tests are carried out with variations in spindle rotation speed and cutting depth to obtain vibration characteristics during the turning process. The results of the study are expected to be able to provide information on the condition of the lathe's vibration so that it can support monitoring machine conditions, preventive maintenance, and improving the quality of the turning process.